2020
DOI: 10.1186/s12891-020-03422-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect modifiers of antibiotic treatment in patients with chronic low back pain and Modic changes - secondary analyses of a randomised, placebo-controlled trial (the AIM study)

Abstract: Background: Randomised trials on antibiotic treatment for patients with chronic low back pain and vertebral endplate changes visible on MRI (Modic changes) have shown mixed results. A possible explanation might be a real treatment effect in subgroups of the study populations. The purpose of the present study was to explore potential clinical effect modifiers of 3-months oral amoxicillin treatment in patients with chronic low back pain and type I or II Modic changes at the level of a previous lumbar disc hernia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…The present results support the previous clinical results of the AIM study, which did not show clinically important effects of amoxicillin compared to placebo 19,36. Interestingly, our results do not suggest a biological effect of amoxicillin on MC edema in the small subgroup with the most abundant edema at baseline 20.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results support the previous clinical results of the AIM study, which did not show clinically important effects of amoxicillin compared to placebo 19,36. Interestingly, our results do not suggest a biological effect of amoxicillin on MC edema in the small subgroup with the most abundant edema at baseline 20.…”
Section: Discussionsupporting
confidence: 91%
“…The present results support the previous clinical results of the AIM study, which did not show clinically important effects of amoxicillin compared to placebo. 19,36 Interestingly, our results do not suggest a biological effect of amoxicillin on MC edema in the small subgroup with the most abundant edema at baseline. 20 We cannot exclude the possibility that MC edema may require a longer time to decline in response to amoxicillin treatment in lowgrade infectious discitis.…”
Section: Interpretation and Implicationscontrasting
confidence: 71%
“…It has been shown that in a certain subset of patients, antibiotic treatment was effective to reduce pain as well as disability ( Albert et al, 2013a ; Gilligan et al, 2021 ). However, this result has failed to be replicated in subsequent studies ( Bråten et al, 2020 ).…”
Section: The Shift From Anabolism To Catabolismmentioning
confidence: 95%
“…Finally, they proved the effectiveness of the antibiotics for Modic type 1 clinically. On the other hand, recently, a double-blind parallel-group multicentre trial to confirm the effectiveness of antibiotics for Modic changes (27). They included 180 patients, and the patients were divided into antibiotics and placebo groups.…”
Section: Antibiotics To Modic Type 1 Changementioning
confidence: 99%